On the wages of temporary help service workers in Germany - Michael Kvasnicka; Axel Werwatz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
This paper produces first econometric estimates for Germany of the contemporanous wage gap associated with Temporary Help Service (THS) employment, as well as the long-term effects of THS work on the future earnings of workers. In addition, we present evidence showing that average male real earnings in the THS industry have declined by about 9% in the period 1975-1995. Our estimates of the overall and group-specific wage gaps attached to THS work are large, albeit significantly smaller than those cited in the existing descriptive literature. Moreover, we find no evidence for any discernable negative average long-term earnings effects of THS work. If anything, THS work seems to have aided workers in putting to a halt declines in their relative earnings observable before joining the THS market.
urn:nbn:de:kobv:11-10049342
Keywords: J30; J31; J40; 330; temporary help services; wage differential; long-term earnings